PROBLEMATIKA PERIZINAN BERUSAHA SECARA ONLINE - Imran, Imran; Gazali, Gazali; Al-Hasni, Fariz (Universitas Muhammadiyah Tapanuli Selatan, 2023)
OSS business licensing still encounters obstacles, including computer systems between ministries and institutions that are not well connected and very few districts/cities that have a Detailed Spatial Plan (RDTR) as the basis for granting location permits. Entrepreneurs have also complained that the OSS system is difficult to access. Chairman of the Central Java Association of Indonesian Entrepreneurs (Apindo) Frans Kongi stated that there are still a number of problems with the OSS system, for example, entrepreneurs cannot access it, even though all requirements have been met.In addition, the existence of PP No. 5 of 2021 tends to violate laws (UU), especially Law No. 25 of 2007 concerning Investment (Investment Law). This was reinforced by the Chairman of Commission VI of the House of Representatives, Teguh Juwarno, who signaled a violation of the law in the establishment of the OSS Institution. The OSS Institution has emerged to take over the authority of BKPM, while the Investment Law states that investment licensing is the domain of BKPM. Another member of Commission VI of the House of Representatives, Zulfan Lindan, asked that the implementation of the OSS system be revoked because it is considered to hamper the investment process in Indonesia and there is uncertainty over the management of the OSS. All licenses should be returned to BKPM.